Kemampuan Semut Myopopone castanea sebagai Predator Alami Larva Kumbang Tanduk (Oryctes rhinoceros) - Thoriq Atala Sitorus; Makhrani Sari Ginting (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
This study aims to determine the effectiveness of predatory ants Myopopone castanea in preying on Oryctes rhinoceros larvae as a biological control effort in oil palm plantations. The study was conducted at the Indonesian Palm Oil Technology Institute using a non-factorial Completely Randomized Design (CRD) method with four treatments, namely F1 (10 ants), F2 (15 ants), F3 (20 ants), and F4 (25 ants) on 5 larvae, and six replications. The parameters observed included the number of larval deaths, time of death, prey search time, and larval biomass. The research data were analyzed using analysis of variance (ANOVA) and continued with Duncan's test at the 5% level. The results showed that treatments F2, F3, and F4 were able to cause larval mortality to reach 100% within 14 days, while the F1 treatment reached 95%. The F4 treatment showed almost the same results as F3. The fastest average prey search time was found in F4, namely 4.5 minutes, while the average larval biomass was 9.62 grams. Based on the research results, Myopopone castanea ants have the potential to be biological control agents for Oryctes rhinoceros’ larvae.